2017
DOI: 10.1159/000481824
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Role of Cannabinoids during Infectious Disease

Abstract: Although the endocannabinoid system (ECS) is involved in the regulation of several physiological processes, including sleep and the immune response, its role during infections has not been fully studied. It is well known that the use of this drug increases susceptibility to infections because of the impact on the modulation of the immune system. Concerning the medicinal or recreational use of marijuana, its influence on the course of an infection, whether this has been caused by bacteria, viruses, parasites, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 103 publications
1
62
0
Order By: Relevance
“…It is generally accepted that the endocannabinoid system (ECS) consists of the membrane cannabinoid receptors (cannabinoid receptor type 1 [CB1R] and type 2 [CB2R]), endogenous ligands (endcannabinoids), and enzymes responsible for the synthesis and degradation of ligands (18). The collaboration of the ECS in the management and elimination of infectious agents such as viruses, bacteria, and some protozoa is indicated previously (19). Scientific researchers recently showed that the activation of the ECS relieves pain and reduces inflammation in the lungs.…”
Section: Oleoylethanolamidementioning
confidence: 99%
“…It is generally accepted that the endocannabinoid system (ECS) consists of the membrane cannabinoid receptors (cannabinoid receptor type 1 [CB1R] and type 2 [CB2R]), endogenous ligands (endcannabinoids), and enzymes responsible for the synthesis and degradation of ligands (18). The collaboration of the ECS in the management and elimination of infectious agents such as viruses, bacteria, and some protozoa is indicated previously (19). Scientific researchers recently showed that the activation of the ECS relieves pain and reduces inflammation in the lungs.…”
Section: Oleoylethanolamidementioning
confidence: 99%
“…Enzymes in ECS are involved in synthesis and degradation of EC. CB1 and CB2 are activated by various substances such as EC or phytocannabinoids that occur naturally in the cannabis plant or synthetic cannabinoids [12]. The ECS is involved in the regulation of several physiological processes, including sleep and the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Chiurchiu et al, in a similar study, proved a decrease in the IL-6, IL-12, and IFN-α levels in dendritic cells [45]. In regard with the antimicrobial activity of Cannabis sativa extracts, studies have reported antimicrobial characteristics targeting gram-positive (Staphylococcus aureus, Micrococcus flavus, and Baccilus subtilus) and gramnegative bacteria (Proteus vulgaris and Pseudomonas savastanoe), as well as an antifungal activity (Aspergilus niger) [40,[78][79][80][81]. Appendino et al also proved an increased antimicrobial activity for Δ9-THC and CBD on Staphylococcus aureus [82].…”
Section: The Cannabinoid Signaling System and Inflammation-linked Witmentioning
confidence: 91%